Effects of the COVID-19 Pandemic on Gynecological Health: An Integrative Review - Marquini, Gisele Vissoci; Martins, Sérgio Brasileiro; Oliveira, Letícia Maria; Dias, Márcia Maria; Takano, Claudia Cristina; Sartori, Marair Gracio Ferreira (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2022)
Objective To analyze the existing scientific literature to find out if the coronavirus disease 2019 (COVID-19) pandemic has an effect on gynecological health.Search Strategy We performed an integrative review of articles published between April 2020 and April 2021 on the PubMed, SciELO, and LILACS databases, using COVID-19 and the following relevant terms: Menstrual change; Ovarian function; Violence against women; Contraception; HPV; Mental health; and Urogynecology.Selection Criteria Among the eligible studies found, editorials and primary research articles, which describe the dynamics between severe acute respiratory syndrome coronavirus (SARS-CoV-2) infection (the cause of the COVID-19 pandemic) and gynecological health, were included.Data Collection and Analysis Through qualitative synthesis, data were extracted from the included publications and from guidelines of national and international societies of gynecology.Main Results The 34 publications included in the present study showed that some factors of the SARS-CoV-2 infection, and, consequently, the COVID-19 pandemic, might be associated with menstrual abnormalities, effects on contraception, alterations in steroid hormones, changes in urogynecological care, effects on women's mental health, and negative impact on violence against women.Conclusion The COVID-19 pandemic has significantly impacted the health of women. The scientific community encourages the development of recommendations for specialized care for women and strategies to prevent and respond to violence during and after the COVID-19 pandemic.
Keywords: COVID-19 pandemic; menstrual change; ovarian function; SARS-CoV-2; violence against women; contraception; urogynecology